From grand tour to virtual tour: Italy through the stereoscope in 1900. Issue 3 (2nd July 2016) - Parmeggiani, Paolo
Abstract : In 1903, Underwood & Underwood published Italy through the Stereoscope: Journeys in and about Italian cities, a multimodal set that provided an immersive travel experience by combining the use of a visual device (the stereoscope and stereoviews), localisation tools (the maps), and a written commentary on each view . The paper argues that this 'medium', which was introduced as a realistic and immersive visual reproduction of the world, was an innovative forerunner of modern virtual – reality technologies. The visual three-dimensional effect obtained by the stereoviews is just one of the characteristics meant to enhance the 'virtual' experience of the viewer. The author analyses the rhetorical means, strictly intertwined with the photographic representations, to reinforce the impression and emotion and to replace the physical experience of a tour with that of an armchair travell er . The framing of the picture, the choice of the points of view, and the style of staging and posing the people reveal an international standard. In spite of their claim of realistic representation, this vision is not ideologically neutral, and the analysis of this set reveals the biases and prejudices towards not only strangers but also the 'old' technology of 2D photography . For social and economic reasons, the ancient practice of taking the grand tour faded, but the conspicuous consumption of this medium allowed the middle class to gain cultural capital with a 3D visual tour in order to claim refinement.